Global Buckling Strength of Girts with Inner Flange in Compression - Vu, Huy Hoang; Vu, Quoc Anh; Pham, Cao Hung (Salehan Institute of Higher Education, 2024)
The objective of this paper is to provide guidance on improving the lateral-torsional buckling strength of cold-formed, channel-section wall girts subjected to leeward wind loads, which cause the inner flange to compress. Additionally, it aims to identify the cross-sectional dimensions that most affect this strength. This is necessary due to the observation that the lateral-torsional buckling strength, with the inner flange in compression, of those members is significantly lower than that of the outer flange due to the difference in lateral bracing lengths, which leads to material waste. The available methods for improving the lateral-torsional buckling of girts when the inner flange is in compression were first summarized. Then, a parametric study was performed on three typical channel cross-sections. Sixty-three cases were created by varying flange width, lip length, cross-sectional depth, and thickness within practical ranges. These cases were solved manually for lateral-torsional buckling strengths using Microsoft Excel. The results showed that increasing the flange width is the most effective way to improve the flexural strength without considering the bracing effect of sheathings, Mnl, while increasing the cross-section thickness is the best for the strength considering the sheathing effect, Mn. Therefore, a new asymmetrical section with a larger inner flange width is recommended for girts when Mnlgoverns the strength. Doi: 10.28991/CEJ-2024-010-11-05 Full Text: PDF